2013
DOI: 10.1556/avet.2013.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lignin supplementation of a diet contaminated with Fusarium mycotoxins on blood and intestinal lymphocyte subpopulations in chickens

Abstract: The objective of the study was to investigate the effects of lignin supplementation of a diet contaminated with the Fusarium mycotoxins deoxynivalenol (DON) and zearalenone (ZEA) on peripheral blood leukocytes and duodenal immunocompetent cells in broiler chickens. From day 1 after hatching, all chickens were fed an identical control diet for two weeks. Then chickens of Group 1 continued to be fed the control diet, whereas Group 2 was fed the same diet supplemented with lignin at 0.5% level. Simultaneously, Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…OTA induces intestinal destruction reported in both animals and in vitro intestinal models (Schrickx et al, 2006;Maresca and Fantini, 2010). In vivo it causes intestinal epithelial cell apoptosis, enabling the uncontrolled penetration of undesirable substances and pathogens (Revajová et al, 2013), and thus predisposing to intestinal infections. OTA had harmful effects on chickens even in concentrations as low as 0.05-2 ppm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OTA induces intestinal destruction reported in both animals and in vitro intestinal models (Schrickx et al, 2006;Maresca and Fantini, 2010). In vivo it causes intestinal epithelial cell apoptosis, enabling the uncontrolled penetration of undesirable substances and pathogens (Revajová et al, 2013), and thus predisposing to intestinal infections. OTA had harmful effects on chickens even in concentrations as low as 0.05-2 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…After absorption, OTA is diffused into various organs through the enterohepatic circulation, bound to serum albumins. Several mycotoxins (deoxynivalenol, OTA, aflatoxin B1) induce apoptosis of intestinal epithelial cells, enabling the uncontrolled penetration of undesirable substances and pathogens (Revajová et al, 2013). OTA directly or indirectly affects the host immune response and increases susceptibility to infections (Elaroussi et al, 2006).…”
mentioning
confidence: 99%
“…Three weeks after starting the experimental diets, heterophil phagocytosis percentages (% P) in groups A and Ce3Lig1 were higher (P<0.05, n=8) than in group Ce (Table 2). Revajová et al (2013) used a relatively higher concentration of lignin (0.5 g/100 g diet) for a shorter time (2 weeks) and observed no effect on phagocytosis in 4-week-old broiler chickens compared to the un-supplemented controls. Heterophil oxidative burst activity was higher (P<0.05, n=8) in group A pullets compared to that of pullets in group Ce (Table 2).…”
Section: Heterophil and Lymphocyte Functionsmentioning
confidence: 92%
“…However, proliferation tended to be higher in group A, followed by groups Ce2Lig1, Ce3Lig1, and Ce (Table 2). Revajová et al (2013) have shown that lignin supplementation increases lymphocyte numbers in the villi of the intestinal tract (but not peripheral lymphocytes) and suggested that beneficial bacteria in the gut (Baurhoo et al, 2007) may contribute to the observed effect.…”
Section: Heterophil and Lymphocyte Functionsmentioning
confidence: 99%
See 1 more Smart Citation